Competitiveness of the Hotel Industry: A Knowledge Management Approach - Pinto Gomes Ambrósio, Luís Filipe (2020)
There is also an emerging research agenda on knowledge management within the hotel sector. Hotels are currently increasingly dependent on their competence to possess internal and external knowledge, making knowledge a critical resource for competitiveness and obtaining competitive advantages for innovation and differentiation of its competitors. Strategies tacit-oriented and explicit-oriented knowledge also has the dominant role in hospitality service operations. The principal goal of this study is to identify the role of knowledge management organizational processes as a determinant of competitiveness in the hotel industry, particularly how knowledge management strategies centered on the source (internal and external) and knowledge (tacit and explicit) have positive an impact on the competitiveness of hotels. We use a quantitative approach based in an email survey applied to 55 Portuguese hotels. Our results show that knowledge management strategies oriented to source and type of knowledge are critical for hotels competitiveness and obtaining competitive advantages.